2016
DOI: 10.1111/vec.12466
|View full text |Cite
|
Sign up to set email alerts
|

The use of rivaroxaban for the treatment of thrombotic complications in four dogs

Abstract: This is the first published report of the use of a new oral direct factor Xa anticoagulant in dogs in a clinical setting for the treatment of both pulmonary and systemic thrombosis. In this case series, we share our limited experience in the use of this new medication, our strategy in determining appropriate dosages, and our monitoring protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 17 publications
6
62
0
3
Order By: Relevance
“…Previous studies in dogs have reported a mild to moderate interindividual variability, and the dosage could be appropriately adjusted by interpreting the PT results in a clinical setting . Although the exact reason is not known, interindividual variability also was detected in our study.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies in dogs have reported a mild to moderate interindividual variability, and the dosage could be appropriately adjusted by interpreting the PT results in a clinical setting . Although the exact reason is not known, interindividual variability also was detected in our study.…”
Section: Discussionsupporting
confidence: 53%
“…These anticoagulants have wide safety margins, making them safer for use than earlier anticoagulants. Rivaroxaban is a novel PO direct factor Xa anticoagulant that decreases the risk of stroke and systemic embolism in human patients with nonvalvular atrial fibrillation and also is used for the prophylaxis and treatment of deep vein thrombosis and pulmonary embolism . Unfortunately, rivaroxaban has not been widely used in clinical settings in veterinary medicine …”
Section: Introductionmentioning
confidence: 99%
“…; Yang et al . ). As PT/PTT are not recommended for assessing the effectiveness of RIV and there are other more accurate tests (anti‐Xa assays) which were not performed in this study and is not widely available, it is difficult to determine if there truly was no clinical anti‐coagulant effect at this dose.…”
Section: Discussionmentioning
confidence: 97%
“…; Yang et al . ; Conversy et al . ) as there was one episode of vomiting but no biochemical abnormalities identified on CBC or serum chemistry profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation